Model Pembelajaran Learning Cycle (Lc) 7E Pada Pokok Bahasan Jamur - HANA SUMIATI WIDJAJA (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2019)
This study was to study the influence of the 7E Learning Cycle (LC) model (obtain, involve, discuss, explain, discuss, discuss, expand, and understand), class 10 learning activities. The sampling method was carried out using saturated sampling techniques, the results showed thus the 7E Learning Cycle (LC) learning module can be used on the subject of mushrooms by looking at 3 aspects of values, namely cognitive, psychomotor and effective